PENERAPAN STANDAR AKUNTANSI KEUANGAN DALAM MENYUSUN LAPORAN KEUANGAN PADA KOPERASI BINA MANDIRI - Putri Utami, Ayu Wandika (Paser Institute Of Accounting and Finance, 2023)
This research aims to determine the application of accounting standards for the financial statements of the Bina Mandiri Cooperative. The analytical method used is descriptive qualitative, namely the activity in the analysis, namely carrying out data reduction. After the data has been reduced, the next stage is data presentation and decision making. After the research data is collected, the researcher will process and analyze the data in a qualitative descriptive manner by describing the condition of the object under study based on existing facts, by collecting data in the form of interview results by combining them with written data sources in the form of documents and drawing conclusions. based on data reduction and data presentation which is the answer to the problem in research. The results of this research show that the application of financial accounting standards in preparing financial reports for the Bina Mandiri cooperative has not been fully implemented and in fact the Bina Mandiri cooperative has not prepared complete financial reports in accordance with financial accounting standards which are guided by SAK ETAP. and the financial recording that is carried out is still using a manual system where recording cash in and cash out is still manual or using a book to record all transactions and then type them using a computer.